TANGGUNG JAWAB NOTARIS DALAM PENYALAHGUNAAN KEADAAN TERKAIT PERJANJIAN PENGIKATAN JUAL BELI (PPJB) DALAM KLAUSUL UTANG PIUTANG - Anwar, Ayrell Raychan; Yudha Cahya Kumala,; Yuliana Setiadi, (Journal of Innovation Research and Knowledge, 2025)
The Sale and Purchase Agreement (PPJB) is commonly used in property transactions as a preliminary step before the execution of a Sale and Purchase Deed (AJB). However, it often contains debt clauses unilaterally drafted by developers, which may disadvantage consumers. The research problems formulated in this study are: (1) What is the notary’s responsibility in relation to PPJB that contains elements of a loan clause? (2) What are the legal consequences of a PPJB that involves elements of abuse of circumstances? The theories used in this is research are theory of responsibility by Immanuel Kant and theory of consequences by Soerjono Soekanto The method used in this research is normative juridical research, specifically a library law research or secondary data with primary. Secondary and tertiary legal sources. As for the research approach used statute approach, analytical approach, case approach, conceptual approach and the method of collecting the legal materials and carried out by identifying and taking inventory of positive law, journals, and other legal resources. The method used in analyzing the legal materials grammatical interpretation, systematical interpretation, and law construction methods. The findings indicate that notaries bear legal, social, and moral responsibilities in drafting (PPJB) that conceal loan agreements. Based on Immanuel Kant’s perspective, notaries are ethically and morally obligated in every action. Meanwhile, Soerjono Soekanto asserts that legal consequences extend beyond the private realm to include social impact, as reflected in Supreme Court decisions annulling PPJBs containing elements of abuse of circumstances.